Antecedents and consequences on employee turnover intention in the hospitality industry in Lebanon - Baajour, Maya (2020)
Purpose: Turnover intention is a very serious problem that hospitality industry faces. It’s a vital aspect to study because it has a huge effect on both the organization and the employee. The organization will lose its highly qualified employees, leaving it with poor productivity and reputation, while the employees will lose their jobs and incomes. The purpose of this research is to study the effect of two variables which are perceived availability of training (PAT) and perceived supervisor support for training (PSST) with turnover, addition to studying the mediating effect of affective commitment (AC). This is important because it’s a win-win situation for both the organization and the employees; the organization will know whether these two perceptions have an effect on employees, and the employees will gain an opportunity to gain more training and support. Design/methodology/approach: A questionnaire was considered as a tool to collect data from employees working in different hotels, restaurants, and tourism companies in Lebanon. VIII A total of 250 questionnaires were collected. The data were analyzed using SPSS Software and the hypothetical model was tested using Onyx. Findings: The finding of the research supported all three hypotheses. H1 (There is an indirect relationship between PAT and Turnover) showed a significant result that when training is available employees’ intention to leave decreases. As for H2 (AC mediates the relationship between PAT and Turnover) it was supported as AC highly mediated the relationship between these two variables; it showed then when training is available, employees tend to be more committed to their organization and their intention to leave decreased. The third hypothesis, H3 (AC mediates the relationship between PAT and PSST with Turnover), was also supported and it showed a higher significant result with PSS. Originality/value: The importance of this study is to show that maximizing the availability of training and supervisor support results in a higher level of commitment and helps in decreasing turnover in the hospitality industry organizations. This research adds a value to the literature gap since limited research was done on the hospitality industry in Lebanon.